(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency of common blood transfusion reactions observed among multi-transfused thalassaemic patients in Sir Ganga Ram Hospital Lahore. Methods: In this cross sectional comparative study, total of 122 thalassaemic patients attending Sir Ganga Ram Hospital Lahore were conveniently selected. Participants were interviewed about transfusion related reactions, using a pre-tested semi-structured questionnaire, after taking verbal informed consent. Patient’s records were also reviewed for clinical manifestations, treatment modalities and laboratory investigations. Data was edited and analyzed using SPSS version -17. Information was described in terms of frequencies and percentages. Statistically significant difference in proportions was analyzed using Chi-Square test. A p-value of less than 0.05 was taken as significant. Results: Of one hundred and twenty two thalassaemic patients, 99(81%) had thalassemia major and among them 62% required blood transfusions at least every fortnight. Proportions of males and females were 52% and 48% respectively. Mean age of these patients was 16 years with 47% and 29% belonged to B-positive and O-positive blood groups. Most commonly reported blood transfusion related reactions were fever (59.8%), rigors (43.5%), itching (25.4%), vomiting (28.7%), body aches (55.7%), back pain (59.8%), dyspnea (27.9%), lack of energy (55.7%), tachycardia (38.5%), cold extremities (50%), and abdominal pain (22.1%). No statistical difference was found between age and occurrence of these reactions, whereas symptoms of itching, back pain and tachycardia differ significantly (p<0.05) between Thalassemia major and Thalassemia intermedia patients. B positive and O positive patients had statistically significantly higher proportion of lack of energy and pain in side of back after blood transfusion (p <0.05). Conclusion: Non-haemolytic reactions like fever, rigors and back pain are the most commonly occurring immediate complications among multiple-transfused thalassaemic patients. Blood transfusion reactions require immediate recognition, laboratory investigation, and clinical management among thalassemias.